2013
DOI: 10.4236/ojvm.2013.32018
|View full text |Cite
|
Sign up to set email alerts
|

Genital and Extragenital Canine Transmissible Venereal Tumor in Dogs in Grenada, West Indies

Abstract: Transmissible venereal tumor (TVT) is a widely reported transplantable tumor in dogs, with no breed or sex predilection and with a low metastatic rate. This retrospective study conducted from 2005 and 2011 sought to evaluate the total number of TVT cases, and to report extragenital TVT lesions in dogs from the small tropical island of Grenada, West Indies. Evaluation of the biopsy and necropsy specimens from dogs with TVT was carried out by cytological and histopathological methods. In the present study, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 13 publications
8
22
0
3
Order By: Relevance
“…In the current case, diagnosis of TVT was confirmed by histopathology that was similar to previous reports [3,9,11] . We observed a large number of the round cells with a prominent nucleolus and basophilic cytoplasm on cytology.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In the current case, diagnosis of TVT was confirmed by histopathology that was similar to previous reports [3,9,11] . We observed a large number of the round cells with a prominent nucleolus and basophilic cytoplasm on cytology.…”
Section: Discussionsupporting
confidence: 86%
“…Primary extragenital involvement is almost rare. Compared to our results, Chikweto et al reported 19.2% of dogs with TVT in extragenital sites in the nasal cavity, eye orbit, spleen, liver, skin, ribs, subcutaneous, submandibular, cervical and inguinal lymph nodes [3] . He also found evidence of metastasis to the ovaries in two dogs.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations